Effect of Diet Supplemented By Earthworm (Eisenia Andrei) Flour on Growth and Hepatic Parameters in Mice - Cova, José Angel; Medina, Ana Luisa; Petrosimo, Pierina; Bastardo, Hilda; Bianchi, Guillermo; Rondon, Miguel; Borges, Lerida (Boletín del Centro de Investigaciones Biológicas)
We studied the effect of diets, supplemented with different percentages of earthworm (Eisenia andrei) flour, on growth, hepatic profile and blood cholesterol levels in mice. Three diets were used: one control diet and two experimental diets with a 25%:75% and 50%:50% earthworm flour:fish flour ratio. Mice were fed the diets for 28 days, and diet materials were analyzed to verify their nutritional content. Size and weight were determined at 0, 7, 14, and 28 days. On day 28, a blood sample was taken to measure the transaminase ALT enzyme and liver biopsies were analyzed using the nonalcoholic fatty liver disease (NAFLD) score. Results showed that both experimental diets were high in protein, an indispensable nutrient for growth in mice. There were no significant differences in size or ALT transaminase. Weight and serum cholesterol showed significant differences. Changes in the NAFLD score of the animals were not observed. The use of earthworm flour in these diets did not alter growth or hepatic tissue in mice.